Analisis Kepuasan Mahasiswa Stmik Rosma Dalam Pemanfaatan Akun Instagram @Stmikrosmaofficial Menggunakan Teori Uses And Gratifications - Lila Setiyani; M. Wahidin; Finna Puspita Priasih Kriswanto (Jurnal Interkom: Jurnal Publikasi Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2023)
The Instagram account @stmikrosmaofficial is an account that provides academic and non-academic information about STMIK Rosma Karawang with the hope of helping answer the information needs of students, lecturers, alumni and prospective new students. This study aims to find out how STMIK Rosma Karawang student satisfaction is in utilizing the @stmikrosmaofficial Instagram account using the Uses and Gratifications theory. To find out student satisfaction, researchers used the expected satisfaction variables (gratifications sought) and satisfaction obtained (gratifications obtained). This research involved followers of the Instagram account @stmikrosmaofficial as a data source and with a sample of 100 STMIK Rosma Karawang students. Survey techniques were used for data collection. The results of the study show that in its use, the @stmikrosmaofficial Instagram account has met the expectations of STMIK Rosma Karawang students. This is evidenced by the acquisition of the expected satisfaction value (gratifications sought) equal to the satisfaction value obtained (gratifications obtained), which is 1485, moreover on the personal identity indicator the Instagram account @stmikrosmaofficial managed to exceed the expectations of its followers and is proven by the satisfaction obtained (gratifications obtained ) worth 396 has exceeded the expected satisfaction (gratifications sought) which is worth 392.